Os dons do espírito: o fenômeno do carismático em Corinto e no nosso contexto eclesial - Feil, Maria Lucena (2012)
Corinth, the third largest city of the Roman Empire, was constituted by many peoples, cultures, philosophies, religions, lifestyles, and known as the most Hellenistic cities of the NT. It was a cosmopolitan city mediated by the elite, dominated by foreign powers, intellectually alive, materially prosperous and morally corrupt. The ideal of the Corinthians was the development of the individual. The city reconstructed in the 44th C, was populated by veterans, people of lower social classes, freed from Rome, disinherited Roman slaves, apart from supportive communities and traditions that constitute their identities. The patronage was the dominant system of slavery. Corinth was submitted to Rome and had Latin as official language. It was consolidated the mystery cults. The Christian community in Corinth opposed to the context as an alternative society. The gifts and charisms of the Spirit become a fundamental discussion, as 1 Cor 12-14. Paul points out in defense of the charisms of the building and submit the other gifts to the agape. The Triune God is the foundation of the charisms which the unity of his acts and be distributes a diversity of charisms and gifts in order to meet the needs of the people of God. The phenomena charismatic / Pentecostal witness wars, mass migrations, natural disasters and the social, philosophical and theological, historical contexts that involve profound changes in the being and the human community. The ecstasy marks the history over the centuries and is also one of the expressions of Catholicism today, the historic churches, as well as the diversity of Pentecostal churches and theological approaches.